Breaking down the cell wall: Still an attractive antibacterial strategy - Zhou, Jingxuan; Cai, Yi; Liu, Ying; An, Haoyue; Deng, Kaihong; Ashraf, Muhammad Awais; Zou, Lili; Wang, Jun (Frontiers in Microbiology, 2022)
Since the advent of penicillin, the humans discovered the phenomenon of bacterial inhibition via antibiotics and explored more. However, with changes in the global environment and the abuse of antibiotics, resistance mechanisms have been selected in bacteria, throwing the global medical and health system in huge threats and challenges. Thus, the study and development of new antimicrobials has in unprecedented urgency and difficulty. Bacteria surround themselves with a cell wall to maintain cell rigidity and protect against environmental insults. Humans have taken advantage of antibiotics to target bacterial cell wall, yielding some of the most widely used antibiotics to date. Cell wall is essential for bacterial for growth and virulence but is absent from humans, remaining in the high-priority target for antibiotic screening throughout the antibiotic era. Here, we review the extensively studied targets i.e., MurA, MurB, MurC, MurD, MurE, MurF, Alr, Ddl, MurI, MurG, lipid A, BamA in the cell wall originate from the very beginning to the latest developments to elucidate the antimicrobials screening. Furthermore, recent advances including MraY and MsbA in peptidoglycan and lipopolysaccharide, and tagO, LtaS, LspA, Lgt, Lnt, Tol-Pal, MntC, and OspA in teichoic acid and lipoprotein also have been profoundly discussed. The review further highlights that the application of new methods such as macromolecular labeling, compound libraries construction and structure-based drug design will inspire researchers to screen ideal antibiotics.